2002
DOI: 10.1099/00221287-148-11-3365
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and physiological characterization of rpoB mutations that activate antibiotic production in Streptomyces lividans

Abstract: Antibiotic production in Streptomyces lividans can be activated by introducing certain mutations (rif) into the rpoB gene that confer resistance to rifampicin. Working with the most typical (rif-17) mutant strain, KO-417, the rif-17 mutation was characterized. The rif-17 mutation was shown to be responsible for activating antibiotic production and for reducing the growth rate of strain KO-417, as demonstrated by gene-replacement experiments. Gene-expression analysis revealed that introduction of rif into S. li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
(24 reference statements)
0
47
0
Order By: Relevance
“…Similarly, in S. coelicolor A3(2) and S. lividans, alteration at His-437 (corresponding to His-482 in B. subtilis) to Arg or Tyr can suppress the deficiency of antibiotic production resulting from the lack of ppGpp due to relA or relC mutation (9 -11). These results suggest that the mutant RNAPs functionally mimic "stringent" RNAP, leading to the activation of a stringent response-dependent antibiotic biosynthesis pathway (10,11). Although rpoB5 mutation also effectively activated NTD production, the activation mechanism for NTD production in B. subtilis appears quite different from that in Streptomyces spp.…”
Section: Ntd Functions As An Autoinducer For Itsmentioning
confidence: 57%
“…Similarly, in S. coelicolor A3(2) and S. lividans, alteration at His-437 (corresponding to His-482 in B. subtilis) to Arg or Tyr can suppress the deficiency of antibiotic production resulting from the lack of ppGpp due to relA or relC mutation (9 -11). These results suggest that the mutant RNAPs functionally mimic "stringent" RNAP, leading to the activation of a stringent response-dependent antibiotic biosynthesis pathway (10,11). Although rpoB5 mutation also effectively activated NTD production, the activation mechanism for NTD production in B. subtilis appears quite different from that in Streptomyces spp.…”
Section: Ntd Functions As An Autoinducer For Itsmentioning
confidence: 57%
“…Among these, experiments with rifampicin have been the most successful (Hu, Zhang and Ochi 2002;Lai et al 2002;Xu et al 2002). Rifampicin (Fig.…”
Section: Applicationsmentioning
confidence: 99%
“…Jørgensen and his co-workers also found that several rifampicin-resistance mutations (including the S487L mutation) resulted in increased production of extracellular enzymes such as amylase and protease in several Bacillus species (S. T. Jørgensen, personal communication). On the basis of these findings, together with results for Streptomyces species, [15][16][17]19,20) improvement of RNA polymerase by the introduction of a rifampicin-resistance mutation might be a useful approach to realize bacterial capability.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…However, unlike the case of NTD production, the S487L mutation failed to activate another secondary metabolism, bacilysin production. 46) Furthermore, in Streptomyces coelicolor and Streptomyces lividans, alteration at His-437 (corresponding to His-482 in B. subtilis) to Arg or Tyr effectively activated antibiotic production, 15,16,21) whereas these mutations were entirely ineffective in B. subtilis NTD production. This suggests that each rifampicin-resistance mutation has distinct effects in a gene-or organism-specific manner.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation